DNA hybridization assay at individual, biofunctionalized zinc oxide nanowires - Leiterer, Christian; Seise, Barbara; Slowik, Irma; Broenstrup, Gerald; Niepelt, Raphael; Weber, Karina; Ronning, Carsten; Christiansen, Silke; Fritzsche, Wolfgang (Journal of Biophotonics, 2013)
Reliable and efficient identification of DNA is a major goal in on-site diagnostics. One dimensional nanostructures like nanowires (NW) represent potential sensor structures due to their extreme surface-to-bulk ratio, enabling enhanced biomolecule binding which results in optimal signals. While silicon NW are already well studied, NW made from other materials with promising properties like ZnO are not yet established as NW sensor material for bioanalytics. Here we demonstrate the DNA functionalization of ZnO NW even at the single NW level and their successful application in a DNA hybridization assay. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-07
Keywords: DNA; Hybridization; Silanization; Silicon nanowire; Zinc oxide